A state-dependent non-coaxial model of sand using a modified vertex theory and its FEM application - Wang, Xing; Kong, Liang; Li, Xue-feng; Ma, Wen-guo (Acta geotechnica, 2022)
In this paper, a modified vertex theory is proposed, and then a non-coaxial plastic model of sand is constructed by introducing the proposed theory into a state dependent dilatancy model. The distinctive feature of this model is that non-coaxial plasticity is only given under the principal stress axis rotation condition. The capability of the model to capture the non-coaxial phenomena is verified by the simple shear test. Furthermore, in order to use the established model to analyze the bearing capacity of foundation, the formulas corresponding to the semi-implicit integration algorithm are derived, and then the applicability of the algorithm to the non-coaxial model is evaluated by simulating the simple shear test of a single element. Finally, the effects of non-coaxiality on the bearing capacity of foundation are analyzed and the results show that the introduction of non-coaxial plasticity reduces the overall stiffness of the foundation model, and neglecting the non-coaxial influences may lead to unsafe designs.